PENGARUH VOLUME PENJUALAN TERHADAP SISA HASIL USAHA (SHU) PADA KOPERASI UNIT DESA SARWA MUKTI CISARUA KABUPATEN BANDUNG :SURVEI DILAKUKAN PADA LAPORAN LABA RUGI PERIODE 2005-2010 - Tika Karinawati, - (2012)
With the acquired the rest of the business result (SHU) a cooperative can maintain viability on an ongoing basis. SHU can be obtained from the total value of sales or acceptance of goods or services in a period. High volume of sales showed that sales made the cooperative done efficiently. This research aims to find out the size of the volume of sales on KUD Sarwa Mukti, knowing acquisition SHU KUD Sarwa Mukti, and figure out the influence of the sales volumes of SHU KUD Sarwa Mukti. Based on these goals the authors choose the method of verifikatif research and quantitative design of research. To support the success of this study the author collected data through existing documents in the form of balance sheet and the profit-loss statement 2005-2010. To manipulate the data they used simple linear regression analysis. The conclusions of these research result show that, the volume of sales, have positive impact on the rest of business result (SHU). Advice from the research include : (1) Cooperatives need to revisit and continue to increase the sales of assets in order to produce optimal SHU (2) Increased and improved sales policy so that it can generate embedded sale volume that efficient (3) Increased the volume of sales and income from each business unit by means of improving the quantity and quality of each business unit who is owned by KUD Sarwa Mukti (4) For the next researcher, the author suggests to expand the object of the research in order to study how things were done to cooperatives in Indonesia. Keyword : Sales of Volume, The Rest of The Business Result (SHU)